Synthesis of 2-Chloro-2′-Deoxyadenosine (Cladribine) and New Purine Modified Analogues - Sivets Grigorii; Sivets Aleksey (Journal of New Developments in Chemistry, 2021)
Theefficient two-step synthesis of 2-chloro-2′-deoxyadenosine (cladribine) via the anion glycosylation of purine potassium salt with the glycosyl chloride in binary solvent mixtures is described. A new method for preparation of diprotected 2-chloro-6-fluoropurine 2′-deoxy-β- D-riboside was developed by treatment of the 2,6-dichloropurine precursor with diethylaminosulfur trifluoride (DAST). Novel N6-alkylated cladribine analogue was synthesized by amination of acylated 2,6-dihalogenopurine nucleosides. It was found that a mild hydrolysis reaction of acylated 2-chloro-6-fluoropurine 2′-deoxy-β-D-riboside gave rise to new purine hydroxylated nucleoside.
Keywords: Anticancer purine nucleoside